Financial distress and hedging: Evidence from Canadian oil firms - Kun Mo; Farrukh Suvankulov; Sophie Griffiths (Bank of Canada, 2019)
The paper explores the link between financial distress and the commodity price hedging behaviour of Canadian oil firms. Specifically, we argue that the expected costs of financial distress have been associated with the hedging behaviour for Canadian oil firms between 2005 and 2015. We use firm-level annual data for 92 Canadian-based, publicly traded oil extraction companies. Results from Honore's semiparametric model for panel data with fixed effects and Heckman's two-step model show that firms with higher short-term and long-term debt tend to hedge more. Furthermore, an increase in the Altman bankruptcy score by one is associated with the decline of the hedge ratio by 1.2 to 1.7 percentage points.
Keywords: G32; Q40; 330; Firm dynamics; Financial markets